Compositions of REE, K, Rb, Sr, Ba, Mg, Ca, Fe, and Sr isotopes in Antarctic"unique" meteorites - Torigoye,Noriko; Ymamoto,Koshi; Misawa,Keiji; Nakamura,Noboru (National Institute of Polar Research, 1993)
P(論文) The abundances of Mg, Ca, Fe, K, Rb, Sr, Ba, and REE in five Antarctic "unique" meteorites, acapulcoite-lodranite type, Yamato (Y)-74063,Y-74357,Y-8002,and Allan Hills (ALH)-78230,and winonaite type, Y-75300 were determined by isotope dilution mass spectrometry. The Sr isotopic compositions of Y-74063,Y-75300,Y-8002,and ALH-78230 were also measured to investigate the whole-rock Rb-Sr isotopic systematics. In terms of the REE abundance pattern, these meteorites are grouped as follows; (1) Y-74063 and ALH-78230 with chondritic REE patterns, (2) Y-74357 with light REE depletion plus alkali and alkaline earth element depletion, and (3) Y-75300 and Y-8002 with middle REE depletion (V-shaped REE pattern) plus a positive Eu anomaly). The mineralogy of these meteorites is closely related to the above REE classification. The ^<87>Rb-^<87>Sr age determined from 'whole-rock samples' for Y-74063,Y-75300,Y-8002,and ALH-78230 is consistent with their formation of 4.5Ga, albeit with a large uncertainty due to the blank correction. Using the mineral/liquid partition coefficients of trace elements, the petrogenetic model calculations were performed. The results give indication on the origin of these "unique" meteorites. Y-74063 and ALH-78230 could be formed through a small degree of partial melting (less than a few%) from a chondritic starting material. Y-74357 could be formed by a larger degree (12%) of partial melting. On the other hand, the V-shaped REE pattern of the third group (Y-75300 and Y-8002) could not be explained by a simple partial melting process. The V-shaped REE pattern may be explained only by assuming the solid state equilibration within a reservoir with chondritic composition. It is suggested that Y-75300 and Y-8002 might be derived from parental materials depleted in phosphate and clinopyroxene. departmental bulletin paper